2015
DOI: 10.3109/17453674.2015.1018760
|View full text |Cite
|
Sign up to set email alerts
|

Poor prosthesis survival and function after component exchange of total ankle prostheses

Abstract: Background and purpose In failed total ankle replacements (TARs), fusion is often the procedure of preference; the outcome after exchanging prosthetic components is debated. We analyzed prosthetic survival, self-reported function, and patient satisfaction after component exchange.Patients and methods We identified patients in the Swedish Ankle Registry who underwent exchange of a tibial and/or talar component between January 1, 1993 and July 1, 2013 and estimated prosthetic survival by Kaplan-Meier analysis. W… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
28
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(28 citation statements)
references
References 13 publications
0
28
0
Order By: Relevance
“…It is important to realize that the results after revision TAR, as in the above-mentioned study, or the results of ankle fusion as salvage procedure for a failed TAR, are inferior to the results after a primary TAR or primary fusion. Kamrad et al (2015) analyzed prosthetic survival, self-reported function, and patient satisfaction after component exchange in 69 cases in the Swedish Ankle Registry. 24 of these patients had a new failure after a median of 2 years.…”
Section: Disappointing Results After Component Exchange Of Tarmentioning
confidence: 99%
See 2 more Smart Citations
“…It is important to realize that the results after revision TAR, as in the above-mentioned study, or the results of ankle fusion as salvage procedure for a failed TAR, are inferior to the results after a primary TAR or primary fusion. Kamrad et al (2015) analyzed prosthetic survival, self-reported function, and patient satisfaction after component exchange in 69 cases in the Swedish Ankle Registry. 24 of these patients had a new failure after a median of 2 years.…”
Section: Disappointing Results After Component Exchange Of Tarmentioning
confidence: 99%
“…Nieuwe Weme et al (2015) reported a survival rate of 87% in the postfracture group and 79% in the instability group at 6 years. Kamrad et al (2015) , using the failure criteria for TAR as defined by Henricson et al (2011) , found a survival rate of 84% for primary TARs after 5 years and 74% after 10 years in the Swedish Ankle Registry. The survival rates after hip and knee replacement are considerably higher.…”
Section: Survival Rate and Complications Of Tar; Still A Long Way To mentioning
confidence: 99%
See 1 more Smart Citation
“…The reported 5-year survival rate in United Sytes was 90.1% [40] . Kamrad et al found that revision TAA has a 10year survival of 55%, which is lower than the 10-year survival of 74% for primary TAA published from the same registry [41] .…”
Section: Long-term Survivalmentioning
confidence: 87%
“…Controversy exists regarding the most predictable salvage for failed total ankle replacement [18][19][20]. Revision total ankle replacement with soft-tissue release/reconstruction or explantation with tibio-talocalcaneal arthrodesis with bulk structural allograft are the most common procedures performed.…”
Section: Discussionmentioning
confidence: 99%